The evaluation of competencies from the didactic planning. Conceptualization and importance - Caicedo González, Jarrison (2022)
Thinking about competency-based assessment from didactic planning is nowadays a trend that should permeate the academic world, in order to efficiently develop the study plan or educationalprogram that intends to apply assessment as a tool for learning improvement. The purpose of this essay is to provide the reader with a theoretical and conceptual foundation on the evaluationof competencies based on didactic planning. A bibliographic search on evaluation, competencies and didactic planning was carried out in order to give rigor to the arguments presented. Itis then understood that the assessment of competencies from didactic planning is crucial when generating cognitive development strategies because it helps to understand the complexity ofthe teaching-learning process.